Consumer responses to gustatory augmentation in low-sodium foods - Qin, Yu; Velasco, Carlos; Motoki, Kosuke (Journal of business research, 2026)
Reducing high sodium intake is a critical issue, but low-sodium foods are often less favored by consumers. To address this, companies are developing gustatory augmentation products as a potential solution (e.g., products that use microcurrents to stimulate taste receptors in the mouth), which enhances consumers’ salt perception to maintain pleasure while reducing actual salt use. However, how these products influence consumers’ desire to eat and food expectations remain unclear. This research addresses these gaps through three pre-registered online studies employing scenario-based designs. Study 1 found that merely imagining the use of gustatory augmentation products during a meal significantly decreased consumers’ overall desire to eat compared to the regular low-sodium condition. Study 2 explored the psychological mechanism underlying this effect, revealing that this effect was partly mediated by heightened negative self-perceptions. Study 3 examined the moderating role of social context (public, private), showing that public (vs. private) settings magnified the negative self-perceptions associated with these products, further lowering consumers’ desire to eat. This research addresses a critical research gap regarding how consumers respond to gustatory augmentation in low-sodium foods through psychological mechanisms related to self-perceptions.